An Overview of Dimensions of Learning Organization - Rai, Bijaya Kumar (DMC Journal, 2024)
Learning organization (LO) is a new concept in management. It was conceptualized by Senge (1990) and theorized by Watkins and Marsick (1993). Senge proposed 5 dimensions as characteristics, but Watkins and Marsick stated it into 7 dimensions and 2 key performance or output. The main objectives of this study are to postulate, explicitly describe, and provide an overview of the dimensions of learning organizations (DLO). Whereas, it adopted a systematic literature review examining the research method. It is resumed that 19 articles were collected from Google Scholar, Sci-Hub, and Proquest and these were systematically analyzed based on theoretical and behavioral perspectives. The limitations of this study are the applied convenience approach for the collection of articles and the research design method. The dimensions of LO are not far different from the field and organization-wise as there are different learning cultures. The findings show that most dimensions are acceptable, reliable, and valid relationships with an organizational learning culture, and in conclusion, DLO has significance different over the demographically. This study assists all kinds of organizational learning human research development or organizational development by identifying dimensions of LO and developed skills, attitudes, and behaviour of employees and building up continuous competency of the organization in the long term aim.